Noncontrast T1 mapping for the diagnosis of cardiac amyloidosis - Karamitsos, T; Piechnik, S; Banypersad, S; Fontana, M; Ntusi, N; Ferreira, V; Whelan, C; Myerson, S; Robson, M; Hawkins, P; Neubauer, S; Moon, J (2013)
Objectives: This study sought to explore the potential role of noncontrast myocardial T1 mapping for detection of cardiac involvement in patients with primary amyloid light-chain (AL) amyloidosis. Background: Cardiac involvement carries a poor prognosis in systemic AL amyloidosis. Late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) is useful for the detection of cardiac amyloid, but characteristic LGE patterns do not always occur or they appear late in the disease. Noncontrast characterization of amyloidotic myocardium with T1 mapping may improve disease detection. Furthermore, quantitative assessment of myocardial amyloid load would be of great value. Methods: Fifty-three AL amyloidosis patients (14 with no cardiac involvement, 11 with possible involvement, and 28 with definite cardiac involvement based on standard biomarker and echocardiographic criteria) underwent CMR (1.5-T) including noncontrast T1 mapping (shortened modified look-locker inversion recovery [ShMOLLI] sequence) and LGE imaging. These were compared with 36 healthy volunteers and 17 patients with aortic stenosis and a comparable degree of left ventricular hypertrophy as the cardiac amyloid patients. Results: Myocardial T1 was significantly elevated in cardiac AL amyloidosis patients (1,140 ± 61 ms) compared to normal subjects (958 ± 20 ms, p < 0.001) and patients with aortic stenosis (979 ± 51 ms, p < 0.001). Myocardial T1 was increased in AL amyloid even when cardiac involvement was uncertain (1,048 ± 48 ms) or thought absent (1,009 ± 31 ms). A noncontrast myocardial T1 cutoff of 1,020 ms yielded 92% accuracy for identifying amyloid patients with possible or definite cardiac involvement. In the AL amyloidosis cohort, there were significant correlations between myocardial T1 time and indices of systolic and diastolic dysfunction. Conclusions: Noncontrast T1 mapping has high diagnostic accuracy for detecting cardiac AL amyloidosis, correlates well with markers of systolic and diastolic dysfunction, and is potentially more sensitive for detecting early disease than LGE imaging. Elevated myocardial T1 may represent a direct marker of cardiac amyloid load. Further studies are needed to assess the prognostic significance of T1 elevation. © 2013 American College of Cardiology Foundation.